Analisis Strategi Pemasaran untuk Pengembangan Usaha Konveksi “Ad Produksi” Malang - Alif Maulana Akbar; Mohammad Maskan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Marketing plays a vital role in enhancing business competitiveness, particularly in dynamic market environments. This study investigates the implementation of the marketing mix strategy (7P) in AD Produksi, a garment manufacturing business in Malang specializing in ready-to-wear clothing. The objective is to identify suitable pricing and promotional strategies to address recent sales stagnation. A qualitative descriptive method was employed, using interviews, observations, and documentation as data collection techniques. The analysis was conducted using a SWOT framework to determine a more effective marketing strategy. The findings reveal that AD Produksi's business falls into SWOT quadrant III, indicating the need to minimize internal weaknesses while leveraging external opportunities. The study recommends adopting competitive and flexible pricing strategies, such as volume discounts and bundled offers. In terms of promotion, the use of social media platforms like Instagram and TikTok, alongside e-commerce platforms such as Shopee, is crucial for enhancing product visibility. Allocating budgets for digital advertising is also suggested to maximize promotional impact. The research implies that aligning pricing with competitor analysis, utilizing technology to boost efficiency, and strengthening brand presence through optimized digital marketing are essential for AD Produksi’s business growth.